The Role of Higher Education in Reproduction of Social Inequality in the Labor Market of Kazakhstan - M. K. Shnarbekova (Moscow Polytechnic University, 2021)
The author analyzes how the modern education system contributes to the formation of socio-economically determined choice of higher education, where the latter includes a decision on continue studying, choosing a university and specialty.The functioning of the higher education system is analyzed in the context of the interconnections of education, the labor market and family resources, which reflect the movement of human capital and current trends in social mobility in Central Asia, as exemplified by Kazakhstan.The article presents data from a study conducted among young professionals aged 21 to 29 years with a different level of education. The sample represents the Republic of Kazakhstan and amounts to 1000 respondents. The survey was conducted using the technique of personal formalized interviews at the respondents' work place.The data obtained indicate that the expansion of accessibility of higher education in Kazakhstan is accompanied by its stratification, which is projected in the inequality in the labor market for young people with a different «background» of family capital. This trend is hidden. The family's resource capital affects the range of choice of educational trajectory (level of education, university, specialty), in the future, the level of education and prestige of a young specialist's university determine career opportunities.